FLQAI – A Questionnaire on Quality of Life in Fecal Incontinence: German Translation and Validation of Rockwood et al.’s (2000) Fecal Incontinence Quality of Life Scale (FIQLS) - Ahnis, A.; Holzhausen, M.; Rockwood, T. H.; Rosemeier, H.-P., [†] (Zeitschrift für Gastroenterologie, 2012)
Aim: The aim of the study was to produce a German version (FLQAI) of the Fecal Incontinence Quality of Life Scale (FIQLS) by Rockwood et al., an English-language measure of quality of life in fecal incontinence 1. The FIQLS has 29 items assigned to the four subscales of lifestyle, coping/behavior, depression/self-perception and embarrassment.Material and Methods: The FIQLS 1 was translated into German and adapted. Indicators of test quality (convergent and discriminant validity, reliability, confirmatory factor analysis) were determined in N = 88 subjects (mean age = 71.5 years) with fecal incontinence and urinary incontinence (control group, n = 29). Results: Three of the four scales of the FLQAI had an acceptable internal reliability. The scales of the FLQAI showed significant correlations with selected subscales of the SF-36 2, the ADS 3 and the FISI 4 (convergent validity). Two of the four scales of the FLQAI discriminated between patients with fecal incontinence and patients with urinary incontinence (discriminant validity). The confirmatory factor analysis did not reveal a uniform fit of the data obtained with the German version with the original four-factor solution of the original version of the questionnaire. Discussion: The Questionnaire on Quality of Life in Fecal Incontinence (FLQAI) is a German-language self-rating questionnaire with satisfactory psychometric properties for measuring disease-specific quality of life in elderly patients with fecal incontinence.
Keywords: fecal incontinence; disease-specific quality of life; questionnaire